Pronunciation in Foreign Language Teaching - Silverio Pérez, Tania (Rastros Rostros, 2014)
Treatment of the phonetic aspect of language has been marginalized in classes of Spanish as a ForeignLanguage (sfl). Although there has been an attempt to reestablish its importance, this has not leadto effective, material changes in teaching. Factors such as undervaluing pronunciation in settings oflanguage teaching, the complexity of the corresponding content, and the methodological disorientationof teachers have all contributed to the current situation. We must therefore revisit the concept in foreignlanguage teaching as a phenomenon within itself, and as content that should be taught and corrected.This study seeks to reflect on the concepts of pronunciation, pronunciation teaching, and phoneticcorrection based on earlier theories, including the work of Antich et al. —a classic text in the areaof foreign language teaching methodology in Cuba— and other researchers in this area, primarily inrelation to Spanish. It is assumed that pronunciation is an ability that must be taught and developed in the foreign language teaching-learning process in order for students to achieve phonetic competenceas part of their communicative competence
Keywords: correction; teaching; foreign languages; pronunciation